Model Pembelajaran Make A Match Untuk Meningkatkan Minat Belajar Fiqih - Junaidin Basri; Muhamad Gian Gintara (STAI Al-Musaddadiyah Garut, 2026)
Students' interest in learning Fiqh, especially the material on sujud sahwi, sujud syukur, and sujud tilawah, is still relatively low. The pre-cycle questionnaire results showed that only 45.8% of the 39 respondents achieved this. This requires a learning strategy that can create an interactive and enjoyable learning atmosphere. One alternative used is the Make A Match cooperative learning model, which combines learning activities with educational games. The purpose of this study was to describe the make a match cooperative learning method and its effect on students' interest in learning about sujud syahwi, syukur, and tilawah in fiqh lessons. This study used the Classroom Action Research (CAR) method with two cycles, each consisting of planning, action, observation, and reflection stages. Data collection techniques included questionnaires, observation, and documentation. The data were then analyzed descriptively and quantitatively by calculating the percentage of questionnaire results, as well as qualitatively through a description of the observation results and reflections for each cycle. The results showed that students' perceptions of the Make A Match model increased from 45.8% in the pre-cycle to 52.4% in cycle I and reached 76.8% in cycle II. Thus, the Make A Match model proved to be effective in increasing students' interest in learning Fiqh. Keywords: fiqh learning, learning interest, make a match